Evaluating the Impact of Nabila Cantika’s Innovation on Reducing Stunting in the Kawedanan Community Health Center, Magetan, Indonesia - Mastuti Handayani; Astuti Setiyani; Sunarto Sunarto; Nurwening Tyas Wisnu (Health Dynamics, 2024)
Background: Nabila Cantika is an innovation to overcome the problem of stunting. This innovation is in the form of toddler class training involving grandmothers. The training was conducted twice, each lasting 120 minutes. The novelty of the study lies in the involvement of grandmothers in the Toddler class. The purpose of the study was to evaluate the effectiveness of the Nabila Cantika innovation in reducing stunting rates. Methods: This study was descriptive and was conducted at the Kawedanan Health Center, Magetan, Indonesia, from February to May 2024. The study population consisted of 90 stunted toddlers cared for by their grandmothers. Samples were taken from the entire population that met the inclusion criteria. The independent variable was grandmothers who attended the Toddler class. Data collection used observation sheets and secondary data in the form of reports from nutrition officers. Data analysis was carried out descriptively, and the effectiveness of this innovation was tested using the McNemar test. Results: The results showed that the effectiveness of the Nabila Cantika program varied in each village. Before the innovation was implemented, 71 toddlers (78.9%) were classified as short, and 19 toddlers (21.1%) were classified as very short. After the innovation was implemented, out of 71 toddlers who were classified as short, 48 toddlers (67.6%) increased to the normal category, while 23 toddlers (32.4%) were still classified as short. Out of 19 toddlers who were classified as very short, 8 toddlers (42.2%) remained in that category, while 10 toddlers (57.8%) increased to the short category. This program has proven effective in reducing stunting rates with a significance value of 0.000. Conclusion: Nabila Cantika's innovation has proven very effective in reducing stunting rates in the Kawedanan Health Center area. This program needs to be continued and monitored until it reaches the target of zero stunting.